2021
DOI: 10.1111/apa.16031
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 antibodies started to decline just four months after COVID‐19 infection in a paediatric population

Abstract: Aim We evaluated the prevalence of paediatric severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infections using antibody testing and characterised antibody titres by time from exposure. Methods This was a single‐centre, prospective, cross‐sectional cohort study. Patients under 18 years old were eligible to participate if they attended the paediatric emergency department at the tertiary Shaare Zedek Medical Center, Jerusalem, Israel, from 18 October 2020 to 12 January 2021 and required blood tests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
(53 reference statements)
4
19
0
Order By: Relevance
“…In comparison with infections with other viruses, patients infected with COVID‐19 produce neutralizing antibodies at relatively low levels 28 , 29 . Hence, we compared the total RBD‐specific IgG titers induced in mouse sera after vaccination with mCuMV TT ‐RBM to SARS‐CoV‐2 convalescent sera (total of 5 different sera).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with infections with other viruses, patients infected with COVID‐19 produce neutralizing antibodies at relatively low levels 28 , 29 . Hence, we compared the total RBD‐specific IgG titers induced in mouse sera after vaccination with mCuMV TT ‐RBM to SARS‐CoV‐2 convalescent sera (total of 5 different sera).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that neutralizing antibodies against SARS‐CoV‐2 are low in general and wane relatively rapidly 44 ; some patients may even completely lack long‐lasting SARS‐CoV‐2 antibodies 28 , 29 . This may be explained by coronaviruses morphological structure as they are large particles with long spike proteins resulting in RBD trimers spaced by 25 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining these results with ours suggests that the recent surge in breakthrough infections in fully vaccinated individuals is due at least in part to declining levels of antibodies and not solely due to the variant strains of SARS-CoV-2. In a recent single-center, prospective, cross-sectional cohort study, children’s immunity was found to decline 4 months after the COVID-19 infection(Breuer et al, 2021). Lyer et al reported that anti-S-protein antibodies reserved neutralizing abilities and persevered for up to 75 days after SARS-CoV-2 infection in >95% of patients(Iyer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors detected specific IgGs 6 months after infection in children who were either asymptomatic or had mild symptoms [ 34 ]. However, other studies suggested waning of antibody responses in children 4-6 after SARS-CoV-2 infection, while parents had somewhat higher levels, but still waning [ 35 , 36 ].…”
Section: Early Research On the Symptoms And Spreading Of The Sars-cov-2 Among Children And Young Peoplementioning
confidence: 99%